Reliability of Interleukin-6 Alone and in Combination for Diagnosis of Early Onset Neonatal Sepsis: Systematic Review - Eichberger, Julia; Resch, Bernhard (Frontiers in Pediatrics, 2022)
Neonatal sepsis is a major cause of morbidity and mortality in both preterm and term infants. Early onset neonatal sepsis (EONS) presents within the first 72h of life. Diagnosis is difficult as signs and symptoms are nonspecific, and inflammatory markers are widely used to confirm or rule out neonatal sepsis. Interleukin-6 (IL-6) is part of the fetal inflammatory response syndrome (FIRS) and therefore an interesting early marker for neonatal sepsis. For this review IL-6 diagnostic accuracy studies for diagnosing EONS published between 1990 and 2020 were retrieved using the PubMed database. The diagnostic potential of IL-6 was analyzed systematically in term and preterm infants, cord and peripheral blood and in dependence of timing of sample collection. Sensitivity and specificity were reported and subgroup analysis was performed. A STARD checklist adapted for neonates with neonatal sepsis was used for quality assessment. We identified 31 studies on IL-6 diagnostic accuracy for EONS diagnosis between 1990 and 2020 including a total of 3276 infants. The range of IL-6 sensitivity and specificity in neonatal samples was 42.1% to 100% and 43% to 100%, the median values were 83% and 83.3%, respectively. IL-6 accuracy was better in preterm infants than in mixed study populations. Early sample collection at the time of sepsis suspicion had the highest sensitivity when compared to other time points. Cord blood IL-6 had higher diagnostic value compared to peripheral blood. The biomarker combination of IL-6 and CRP was found to be highly sensitive, but poorly specific. We concluded that IL-6 has a good performance as an early diagnostic marker of EONS within a study population of preterm infants, with best results for cord blood IL-6 using cut-off values above 30 pg/mL.